The Role of Phosphatidylinositol Phosphate Kinases during Viral Infection - Anne Beziau (Viruses, 2020)
Phosphoinositides account for only a small proportion of cellular phospholipids, but have long been known to play an important role in diverse cellular processes, such as cell signaling, the establishment of organelle identity, and the regulation of cytoskeleton and membrane dynamics. As expected, given their pleiotropic regulatory functions, they have key functions in viral replication. The spatial restriction and steady-state levels of each phosphoinositide depend primarily on the concerted action of specific phosphoinositide kinases and phosphatases. This review focuses on a number of remarkable examples of viral strategies involving phosphoinositide kinases to ensure effective viral replication.